Immune response in a cutaneous allergic drug reaction secondary to imidapril, benazapril and metformin - Ana Maria Abreu Velez; Isabel Cristina Avila; Michael S. Howard (Our Dermatology Online, 2013)
Introduction:Cutaneous drug reactions may be classified with regard to pathogenesis and clinical morphology. They may be mediated by both immunologic and non-immunologic mechanisms.Case report:A 56 year old female presented with widespread patches and macules, concentrated on her face, trunk and extremities. The lesions were pruritic, and temporally associated with intake of benzapril hydrochloride, imidapril and metformin.Methods:Biopsies for hematoxylin and eosin (H&E) examination, as well as for immunohistochemistry (IHC) and direct immunofluorescence (DIF) analysis were performed for diagnostic purposes, and also to evaluate the lesional immune response.Results:Hematoxylin and eosin staining demonstrated a histologically unremarkable epidermis. Within the dermis, a moderately florid, superficial and deep, perivascular infiltrate of lymphocytes, plasmacytoid lymphocytes, histiocytes and rare eosinophils was identified, consistent with an allergic drug reaction. DIF demonstrated deposits of IgE, Complement/C3 and fibrinogen around dermal blood vessels. IHC demonstrated positive staining with HAM-56 and myeloid/histoid antigen in the cell infiltrate around the upper dermal blood vessels. HLA-ABC was overexpressed around those vessels, as well as around dermal sweat glands. COX-2 demonstrated positive staining in both the epidermis and upper dermis.Conclusion:Drug reactions are significant causes of skin rashes. In the current case, we were able to identify multiple antigen presenting cells in the area of the main inflammatory process. The immunologic case findings suggest that allergic drug eruptions may represent complex processes. An allergic drug reaction should be suspected whenever dermal, perivascular deposits of fibrinogen, Complement/C3 and other markers such as IgE are identified via DIF.